Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
Marshall Whitney, Judge Leonard Meyers, new President-Elect Rodney Worrel 5080 E. Kings Canyon Road, Fresno